C2 domain plays critical roles in localization of novel C2 domain-containing protein OsC2DP. (2nd November 2019) - Fu, Shan; Huang, Jingjing; Chen, Zhiwei; Xia, Jixing
ABSTRACT: OsC2DP is a cytosolic protein containing a C2 domain recently identified in rice, which is translocated to the plasma membrane in response to salt stress. Here, we further investigated the subcellular localization of OsC2DP by truncation analysis. In consistent with OsC2DP, OsC2DP 1−165 containing C2 domain at the N-terminus was localized to the cytosol. In contrast to OsC2DP 1−165, OsC2DP 166−290 lack of C2 domain at the C-terminus was localized to the cytosol and nucleus, which was similar to the GFP control. Under salt conditions, subcellular localization of both OsC2DP 1−165 and OsC2DP 166−290 was not altered and failed to migrate to plasma membrane. These results indicated that the subcellular localization was determined by C2 domain of OsC2DP under normal conditions and that both N- and C-terminus of OsC2DP are essential for its cytosol-plasma membrane translocation in response to salt stress.